Boundaries Around, Boundaries Within: Introduction to the Thematic Section on the Translation Profession, Translator Status and Identity - Ruokonen, Minna; Salmi, Leena; Svahn, Elin (HERMES - Journal of Language and Communication in Business, 2018)
-